Alcoholic and isocaloric diet, but not ovariectomy, influence the apoptosis of bone cells within the alveolar bone crest of rats - Pereira da Silva Marchini, Adriana Mathias [UNESP]; Goncalves, Lucelia Lemes [UNESP]; Machado Salgado, Miriane Carneiro [UNESP]; Prado, Renata Falchete do [UNESP]; Marchini, Leonardo; Carvalho, Yasmin Rodarte [UNESP]; Rocha, Rosilene Fernandes da [UNESP] (Elsevier B.V., 2014)
Objective: Studies suggest that chronic alcoholism as well as oestrogen deficiencies may affect bones in general, including alveolar bone and, by doing so, increase individuals' susceptibility to develop progressive periodontal disease. This paper aims to verify the influence of chronic alcoholism and/or oestrogen deficiencies in the apoptosis of bone cells of the alveolar bone crest region in rats.Design: Initially, 54 rats were divided into ovariectomized (Ovx) and Sham operated (Sham) groups. Thirty days after surgery, these two groups were equally sub-divided, and received, for 56 days, the following dietary intervention: alcoholic diet (with 20% alcohol solution,), isocaloric diet and ad libitum diet (free diet). Analysis was undertaken by immunohistochemistry, using an antibody to detect apoptosis (anti PARP p-85).Results: When comparing the six experimental groups, no significant differences were observed in the apoptosis of bone cells. Also, there was no significant difference in the quantity of cells undergoing apoptosis when the animals from Ovx groups were compared with those from Sham groups. However, when comparing only different dietary groups, differences were observed between the groups ad libitum and isocaloric, to osteoblasts (p = 0.045); and ad libitum and alcohol, to osteocytes (p = 0.007).Conclusion: It is concluded that ovariectomy was not able to influence the rate of apoptosis of bone cells of the alveolar bone crest region in rats and that a possible influence of diet on apoptosis of osteoblasts and osteocytes cannot be ruled out. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Alcoholism; Ovariectomy; Osteoporosis; Periodontium; Apoptosis